(untitled) (Ajudikasi : Jurnal Ilmu Hukum, 2025)
The purpose of this research is to find out more about land tenure without rights due to illegal acts. The research method used in this research is the empirical research method by taking a qualitative approach. The result of this research is that it is clear that both parties have agreed to exchange their land which has been outlined in the minutes. The agreement occurs when an agreement is reached between the parties making the agreement, so that the perpetrator’s actions are included as unlawful acts. The elements that are fulfilled are the existence of an action that has been carried out by the perpetrator by continuing to control land that does not belong to him; the action must be against the law; and the action causes harm to the heirs. Furthermore, compensation for ownership of land rights due to unlawful acts must compensate the person whose fault caused the loss, either in the form of money or in the form of returning to the original state. The amount of compensation depends on the size of the claim filed by the injured party. The size of the compensation fee is measured by looking at the object of the dispute, the grace period, and the costs incurred in deliberation efforts. However, until now there is no good faith from the perpetrator to return or compensate for his actions